2020
DOI: 10.3389/fmicb.2020.01880
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Clinical and Environmental Strains of Exophiala spinifera by Long-Reads Sequencing and RNAseq Reveal Adaptive Strategies

Abstract: Exophiala spinifera, a capsule-producing black yeast, is overrepresented as agent of disseminated infection in humans with inherited dysfunction of the CARD9 gene. In a review of published caspase recruitment domain-containing protein 9 (CARD9) deficiency cases, black fungi were linked to mutations other than those prevalent in yeast and dermatophyte cases, and were found to respond to a larger panel of cytokines. Here, we sequenced and annotated the genomes of BMU 08022 from a patient with CARD9 deficiency an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
(79 reference statements)
1
2
0
Order By: Relevance
“…In addition, we successfully identified the mitochondrial genome with a size of 26,874 bp ( Table 2 ). The assembly size agrees with the size observed in other strains of this genus (20~38 Mb) [ 16 , 36 ]; additionally, the assembly’s completeness and lack of duplicated BUSCO genes strongly suggest that this is an haploid genome version with no evidence of contamination. The small number of fragmented or missing genes within the assembly indicates that it is a valuable resource for gene prediction and functional annotation efforts, with minimal loss of integrity.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In addition, we successfully identified the mitochondrial genome with a size of 26,874 bp ( Table 2 ). The assembly size agrees with the size observed in other strains of this genus (20~38 Mb) [ 16 , 36 ]; additionally, the assembly’s completeness and lack of duplicated BUSCO genes strongly suggest that this is an haploid genome version with no evidence of contamination. The small number of fragmented or missing genes within the assembly indicates that it is a valuable resource for gene prediction and functional annotation efforts, with minimal loss of integrity.…”
Section: Resultssupporting
confidence: 83%
“…Mb) [16,36]; additionally, the assembly's completeness and lack of duplicated BUSCO genes strongly suggest that this is an haploid genome version with no evidence of contamination.…”
Section: Plos Onementioning
confidence: 92%
“…The pseudomycetomatous type of dermatophytosis is mainly observed in patients with underlying disorders, particularly following solid organ transplantation (SOT), but some cases were observed in apparently healthy individuals. In the past two decades, several inherited immune disorders have been discovered, of which mutations in the caspase recruitment protein domain 9 ( CARD9 ) is particularly significant for fungi: dermatophytes are one of the main groups emerging with this disorder [ 8 , 9 ]. Lanternier et al [ 10 ] suggested that all dermatophyte infections with this type of clinical course and where the host was reported as otherwise appearing healthy, actually had a non-diagnosed CARD9 disorder.…”
Section: Introductionmentioning
confidence: 99%